Análise econômico-financeira : estudo de caso entre um banco digital e um banco tradicional nos anos de 2019 à 2021 - Santos, Patrícia dos (2022)
This task has as its aim to analyze the liquidity, solvency and profitability of a traditional bank and also a digital one, in order to get a comparative from the results. It is descriptive research with quantitative approach, related to case study. So, using the economic-financial analysis, it was compared the results got in 2019, 2020 and 2021. In this way, after doing the horizontal and vertical study, it was possible to verify that Nubank S/A has been having a rising in the financial intermediations through these years, but it maintained itself with losses, while, in another hand, Banco do Brasil S/A presented profits. With the liquidity, solvency and profitability, Banco do Brail S/A had better performance comparing to Nubank S/A, when it comes to profitability, although Nubank S/A had presented good results in some indicators, Banco do Brasil got the best performance.